Physicochemical Characteristics of PVDF/ZSM-5 Composite Membrane for Potential Applications in Vanadium Redox Battery - Zaskia Alifia; Michael Julian Haryanto; Devi Ayu Fitriyani; Anung Riapanitra (Jurnal Kimia Sains dan Aplikasi, 2025)
Composite membranes were synthesized using poly-(vinylidene fluoride) (PVDF) and zeolite (ZSM-5) to improve the performance of PVDF as a battery separator. The PVDF-ZSM-5 membranes, prepared with varying concentrations of ZSM-5, underwent characterizations of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). These analyses revealed a notable increase in β-phase formation in PVDF, greater porosity, and improved surface morphology due to the incorporation of ZSM-5. Evaluations of their physicochemical properties showed that these membranes resulted in electrical conductivity up to 96.4 mS/cm, enhanced contact area, porosity reaching 78.61%, and flux value up to 5.4 ×10⁻2 L m⁻2 h⁻2. Adjustments in ZSM-5 concentrations proved instrumental in fine-tuning these performance metrics. These findings highlight the potential of PVDF-ZSM-5 membranes as a cost-effective membrane separator for redox battery systems. This research lays the groundwork for future advancements and broader commercial applications in energy storage technology.